Komunikasi Ritual Tegen Sawa Dalam Upacara Ngaben Di Lingkungan Babakan Gerung - I Komang Widya Purnama Yasa; I Wayan Wirata; I Gusti Ngurah Ketut Putera (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
Communication in a ritual perspective is about the process that occur in religious ceremonies. The process of the ceremony involves the interaction that is carried out by the implementation of ceremonies such as the tegen sawa in Ngaben ceremony at Babakan Gerung, especially in Banjar Suka Wardaya. This ritual is carried out when there are banjar residents who died in a sequent within a few days. The essence of the ritual emphasizes the role of women in shoulder sawa. This study aims to determine the form of communication, communication processes and the meaning of communication that exist in tegen sawa rituals at Ngaben ceremony in Babakan Gerung. This study uses a qualitative paradigm with a phenomenology. Religious theory, symbolic interaction theory, phenomenological theory, and communicative action theory are used in expressing the processes that occur in this ritual. The location of this research is at Banjar Suka Wardaya, Babakan, Gerung Utara, West Lombok. The techniques to collected data in this study is by observation, interviews and documentation. Informants were determined by purposive technique. The results of this study indicate the ritual implementation of tegen sawa performed by women is able to solve the phenomena that occur. The form of tegen sawa ritual communication in the Ngaben ceremony is interpersonal communication and group communication. The communication process that occurred began with a phenomenon that occurred in the community so that the Kelihan Banjar held dialogue with the members of the banjar, the family of the seda and Sulinggih. The ritual is carried out based on mutual agreement and also carried out together by the banjar’s members. The meaning of ritual communication in the ceremony of Ngaben tegen sawa of religious meaning, togetherness, education and social culture.